Direct Election System In City of Makassar In Islamic Law Perspective - Akil Tahir; Lamba Sultan; Darussalam Syamsuddin; Moh Sabri (Lembaga Sembilan Tiga Community, 2019)
Direct Election System in Makassar City in Islamic Law Perspective, this is located in Makassar City, South Sulawesi Province. This type of research is descriptive qualitative. While the approach used in this study is a formal juridical approach. The results of the study indicate that the mechanism of direct elections in Makassar City in accordance with the 1945 Constitution, Article 18 paragraph (4) affirms: